Educational Management Support, Self-Efficacy, and Academic Flow: Evidence from Senior High School Students in Surabaya - Nisrina Sonna Salsabila; Riza Noviana Khoirunnisa (Journal of Educational Management Research, 2026)
Learning at the senior high school (SMA) level represents a critical phase in students’ academic and psychological development. In Indonesia, the senior high school completion rate remains relatively low, indicating the need to examine psychological factors that support students’ optimal learning experiences. This study aimed to analyze the relationship between self-efficacy and academic flow among senior high school students in Surabaya. A quantitative correlational research design was employed, involving 250 students from grades X and XI selected through purposive sampling. Data were collected using self-efficacy and academic flow scales and analyzed using Pearson correlation and simple regression techniques. The results showed a strong and significant positive relationship between self-efficacy and academic flow (r = 0.613; p < 0.01), indicating that students with higher self-efficacy tend to experience higher levels of academic flow. Furthermore, self-efficacy was found to be a significant predictor of academic flow, demonstrating its substantial contribution to students’ engagement in learning activities. These findings imply that strengthening students’ self-efficacy is a crucial psychological and managerial strategy for fostering optimal learning experiences and enhancing academic engagement in senior high school contexts. Educational management practices that support confidence, autonomy, and mastery-oriented learning environments are therefore recommended to improve students’ academic flow